Thermal behavior of coffee oil (Robusta and Arabica species) - Kobelnilk, Marcelo; Fontanari, Gustavo Guadagnucci; Cassimiro, Douglas Lopes [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer Nature, 2013)
Coffee seeds are a source for obtaining oil which is used in the candy, soluble coffee, and cosmetics industries. The main purpose of this study was the investigation of the lipid profile and thermal behavior of the roasted and in nature coffee oil of Arabica and Robusta species, using thermogravimetry, differential thermal analysis, derivative thermogravimetry, differential scanning calorimetry (DSC), and modulated DSC. Details concerning the thermal decomposition as well as data of the kinetic parameters have been described here. The kinetic studies were evaluated from several heating rates with a sample mass of 10 mg in open crucible under nitrogen atmospheres. The obtained data were evaluated with the isoconversional kinetic method, where the values of activation energy (Ea/kJ mol-1) were evaluated in function of the conversion degree (α). In addition, this oil was evaluated by modulated DSC from 25 to -60 °C, where the transition phase behavior was verified. © 2013 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Coffee oil; Kinetic parameters; Thermal behavior; Transition phase